Controle por modos deslizantes e observador de distúrbios aplicados ao motor síncrono de ímãs permanentes - Gabbi, Thieli Smidt (2015)
This master thesis proposes a current control technique based on sliding mode strategy and disturbance observer for high-performance drive applied to permanent magnet synchronous motors and can be extended to other systems. The combination of sliding mode control and disturbance observer applied to the current control presents the characteristics necessary to minimize the coupling between the axes, rejection of external disturbances and parametric variations. A continuous time control scheme is developed, the stability proofs are performed from the Lyapunov analysis. The performance of the propose technique is evaluates through simulation results. Moreover, this master thesis presents a discrete-time sliding mode controller combined with a discrete-time disturbance observer. The development in discrete-time enables the implementation in digital processors. The conditions of reach of the proposed controller considering the transport delay of digital implementation are still evaluated. The stability proofs of the proposed scheme are presented. Simulation results are shown. In addition, it is developed an experimental platform for drive and control of the permanent magnet synchronous motor in which the experimental results are obtained.